Segregation, Flow Properties and Usability of Construction Materials Using Power Plant Solid Waste - Kishor, Chandan; Chawla, Himanshu; Sadhu, Sayan; Mallick, S. S. (My University, 2026)
A vacuum-based segregation tester was designed to understand how bulk solid materials separate under controlled lab conditions. The tester uses a vacuum-driven airflow system to show how particles can be sorted into fine and coarse groups. This helps us grasp segregation behaviors and material handling traits. The design provides a basis for studying how particles interact and finding ways to improve segregation efficiency through better airflow and structural changes. This concept points to the potential for using such a tester in future experiments for classifying materials and construction purposes. This study further investigates the flow properties and segregation tendency of pond ash (PA), pond fly ash (PFA), and flue gas desulfurization gypsum (FGDG), and further investigates the influence of these properties on the mechanical and durability properties of mortar made using these industrial by products. Low-cohesion materials such as PA and FGDG improve workability and transport efficiency. Segregation analysis reveals that PA replacement in mortar leads to particle redistribution, affecting bulk density and particle size distribution, particularly at higher replacement levels. However, there is no significant segregation that affects the dry-mix for construction applications. The major focus of this study is to replace fine river sand with pond ash in the production of plaster. In this study, the physical, mechanical, and microstructure characteristics of mortar are investigated for different replacement levels of sand with pond ash. The findings demonstrate that raising the replacement level lowers the dry density of pond ash mixes. This is because pond ash is more porous and absorbs more water. The study confirms that up to 20% PA replacement enhances compressive and flexural strengths while reducing density, making it suitable for lightweight concrete (Novak 2017) and prefabricated elements. However, excessive replacement (≥30%) results in strength reduction due to increased porosity and ettringite formation. The findings indicate that raising the replacement level lowers the dry density of pond ash mixes, which is caused by the porosity and increased water absorption of pond ash. Notably, the compressive and flexural strengths are greater than those of control specimens at a 20% replacement rate. Conversely, the achieved strength exceeds the strength required by the Indian code, but the drying shrinkage is 31% less than the control. SEM-EDXS demonstrates that samples with a 20% pond replacement have a higher C-S-H gel density, which results in higher compressive and flexural strengths. According to XRD results, the presence of sodium sulphate is the reason for the 40% pond ash replacement's decreased strength. Based on this study, it concluded that fine pond ash can partially replace river sand for internal plastering, as well as for making mortar and blocks. On the other hand, adding FGDG (more than 5%) to the mixture produces most of the ettringite, sulfate and aluminate hydrates, and it shows a higher degree of expansion in the mixture compared to the control, which also reduces the strength. Therefore, the potential of combined pond fly ash (PFA) and flue gas desulfurization gypsum (FGDG) is investigated as a partial replacement for cement by mixing them with fine river sand for mortar development. Due to their finer particles and higher surface area,mixes with PFA and FGDG require more water for the same consistency, yet still show reduced flowability once hydrated. While dry mixes remain uniformly distributed with negligible segregation effect, water addition increases cohesion and lowers workability, which directly affects strength. Experimental results show that mortar containing pond fly ash, FGDG, and cement concentrations of 5 wt.%, 5 wt.%, and 90 wt.% yields the maximum compressive strength (8.9 MPa) and flexural strength (3.4 MPa) after 28 days. This mortar has 12.6% higher compressive strength and 48% lower shrinkage in comparison with control specimens. A reduction in shrinkage is attributed to the denser structure of the mortar, as the calcium silicate hydrate (C-S-H) gel is found to exist in the SEM image and is also identified through XRD studies. Higher concentrations of SO3 were observed to decrease the strength of mortar, highlighting the significance of maintaining the recommended level. FGDG causes an increase in the amount of CaSO4.2H2O, which dilutes the cementitious matrix, reducing its compressive strength. This is because FGDG has sulfate ions that react with some parts of the green mortar, like the aluminite phase of cement, to make ettringite (CaSO4.2H2O). The formation of expansive ettringite results in volume expansion, cracking, and deterioration of green mortar. The application of this mortar can be in the internal plaster, bricks, and masonry. These findings underscore the strategic incorporation of industrial by-products in sustainable construction, optimizing resource efficiency while maintaining mechanical performance and durability. Future research should explore higher replacement levels, long term field performance, and life cycle analysis, promoting the broader application of PA, PFA, and FGDG in eco-friendly infrastructure.
Keywords: segregation; sifting segregation; pond ash; FGD Gypsum; Mortar; powder flow tester